2019
DOI: 10.1063/1.5088517
|View full text |Cite
|
Sign up to set email alerts
|

A fucosyltransferase inhibition assay using image-analysis and digital microfluidics

Abstract: Sialyl-LewisX and LewisX are cell-surface glycans that influence cell-cell adhesion behaviors. These glycans are assembled by α(1,3)-fucosyltransferase enzymes. Their increased expression plays a role in inflammatory disease, viral and microbial infections, and cancer. Efficient screens for specific glycan modifications such as those catalyzed by fucosyltransferases are tended toward costly materials and large instrumentation. We demonstrate for the first time a fucosylation inhibition assay on a digital micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…4,54 However, regions with pointy edges and high electric fields (>108 V/cm) are known to cause a dielectric breakdown, 55 while ″skewed-wave″ edged electrodes have been proven to resolve this problem. 26 Droplet motion on the chip was achieved by actuating the electrodes for 0.7 s at a voltage of 178 V (15 kHz sine wave). To dispense droplets, a larger droplet was initially stretched by actuating four electrodes from the reservoir.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,54 However, regions with pointy edges and high electric fields (>108 V/cm) are known to cause a dielectric breakdown, 55 while ″skewed-wave″ edged electrodes have been proven to resolve this problem. 26 Droplet motion on the chip was achieved by actuating the electrodes for 0.7 s at a voltage of 178 V (15 kHz sine wave). To dispense droplets, a larger droplet was initially stretched by actuating four electrodes from the reservoir.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Adding surfactants to such solutions have proven to be effective even without any filler oil. 26 Hence, 0.05% Tetronic 304 was added to the aqueous cleavage buffer. Although the surfactant resulted in the improved movement of the cleavage buffer droplets (similar to our previous study 26 ), it was observed in this study that the droplets had left traces along their paths, which made chip reuse quite difficult.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Digital microfluidics (DMF) can alleviate the challenges associated with droplet‐in‐channel systems since DMF are able to address each droplet individually. Having this control is especially useful in multi‐step procedures, such as transformation and enzymatic assays, [ 42,43 ] drug and inhibitor screening, [ 44 ] and gene‐editing [ 27 ] Recently, we have combined both of these platforms together, in which we call a “hybrid” microfluidics, placing co‐planar electrodes (i.e., ground and activated electrodes on the same plate) under a network of microfluidic channels to enable individual control of the droplets in the channels. [ 45 ] Given the increased control over droplets and their contents, [ 46–51 ] there is an opportunity to use this hybrid‐based technology as a method to control the isolation of mammalian isoclones.…”
Section: Introductionmentioning
confidence: 99%